Clinical implications of nervus intermedius variants in patients with geniculate neuralgia: Let anatomy be the guide. Issue 7 (26th December 2019) - Clifton, William E.; Grewal, Sanjeet; Lundy, Larry; Cheshire, William P.; Tubbs, R. Shane; Wharen, Robert E.
Abstract: Geniculate neuralgia (GN) is an uncommon, but severe, condition that is characterized by excruciating paroxysmal pain in the seventh cranial nerve's cutaneous distribution of general somatic afferent fibers carried through the nervus intermedius (NI). GN becomes a surgical disease in refractory cases of pain after exhaustive medical management. Surgical intervention in the form of microvascular decompression and nerve sectioning has been investigated with good patient outcomes. Despite this, there are limited guidelines on either technique's appropriateness in specific operative scenarios. In our 30‐year experience in GNs surgical management, we have found that a detailed knowledge of the NIs anatomy, variants, and intraoperative surgical anatomic findings are the key to choosing the most appropriate intervention, and may provide the answer to why some patients fail to experience pain relief after surgery. These anatomic variants also may explain why many patients commonly do not experience side effects related to the visceral efferent and special afferent fibers after nerve sectioning.